(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
The article discusses about case-study method and explains that it is a tool that allows you to apply theoretical knowledge to solve practical problems. It is mentioned that the method promotes the development of independent thinking in students, the ability to listen and take into account an alternative point of view, and to express their own with reason.